Functional PEG Macromers for Biomedical Applications - Ayhan, Fatma; Ayhan, Hakan (Journal of Composites and Biodegradable Polymers, 2017)
Biomedical technology combines medicine and technology to diagnose, replace damaged site or regenerate tissue, and delivery of bioactive agent in a temporally controlled manner. Modified and unmodified natural and synthetic polymeric biomaterialsare currently formed in various structural shapes and chemical ingredients to overcome challenges. The recent developments in engineered PEG based hydrogel materials shows a great attractive research area due to its relatively high biocompatibility. The synthetic acrylated PEG or PEG-diacrylate and –multiacrylate monomers are the main backbone of photoinitiated radical polymerization of acrylates and polyesters used in non-degradable and degradable biomaterials. The physicochemical properties also enable to reinforce natural polymers structural characteristics. Recently published different classes of materials comprised of acrylated PEG macromers are summarized in this review.